Individualization in Education and Methods of Improving Teaching the English Language - Nozima Rajabboyevna, Alimova (International Journal of Psychosocial Rehabilitation, 2020)
Teacher skills are reflected in the precise lesson planning. The lesson should be planned in such a way that it clearly reflects what is being planned and does not allow for a different plan. Occasionally, there are mistakes in the lesson planning of young teachers and practicing students and this may influence the process of teaching. The article analyzes technology of individualization of education and methods of improvement of teaching as the example of English language.